Effectiveness Of Disclosure In Information Asymmetry In Companies LQ45 - Juniarti Puspita Wulandari; Arifin Siagian; Noviarti Noviarti (JEBIM Prima, 2023)
This study aims to determine the Disclosure of Enterprise Risk Management (ERM) and The Disclosure of Intellectual Capital (IC) that can affect the level of information asymmetry in LQ45 companies in 2019. This study uses multiple linear regression analysis method with data collection on ERM and IC disclosure using content analysis method. The results of this study indicate that ERM disclosure is significantly negatively related to the level of information asymmetry. Meanwhile, IC disclosure has an insignificant negative relationship with information asymmetry. The limitation of this study is that there are other variables that are no less important in determining information asymmetry besides ERM and IC. In addition, the sampling in this study was only limited to 33 samples, due to the limited time that the researcher had. Suggestions from this study are, it is hoped that further researchers can disclose IC and ERM using other methods such as focus groups, panel discussions, and peer reviews so that the results obtained are more objective in using the data.